A novel solid phase extraction Ultra high performance liquid chromatography tandem mass spectrometry method for the quantification of ochratoxin A in red wines - Marino Repizo, Leonardo (2015)
A novel and advanced technology on solid phase extraction column prior to liquid chromatography coupled to tandem mass spectrometry has been used for the determination of ochratoxin A in red wine samples. Due to the need of a reliable and rugged method according to current regulations and with the aim of minimize heuristic efforts associated with analytical method development, the statistical design of experiment was employed. On other hand, the method validation according to European Commission 2002/657/EC was achieved. The values obtained for decision limit (CCa), detection capability (CCb), limits of detection and quantification were 0.07 lg L1, 0.14 lg L1, 0.13 lg L1 and 0.41 lg L1, respectively. The recoveries values were ranged from 95.7% to 107.2%. These values were compatible with the 2.0 lg L1 maximum allowable concentration limit established by different international regulations.